Transparent Aging-Aware Thread Throttling - Medeiros, Thiarles S.; Pereira, Luan; Rossi, Fábio D.; Luizelli, Marcelo C.; Beck, Antonio Carlos S.; Lorenzon, Arthur F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2019)
To satisfy the rising performance demands of modern applications, the number of cores in a single chip package has been increasing. However, the power dissipated and temperature have been growing at a higher rate, accelerating the aging process of new processors. Considering that a significant number of parallel applications are unbalanced, in many cases performance stagnates after a certain number of concurrent threads starts executing. In such cases, the only outcome is a temperature rise on the processor, which drastically accelerates aging. Given that, we propose an automatic and transparent approach to reduce the processor aging by automatically tuning the number of threads for OpenMP applications at run-time. Our tool, Geras, is entirely transparent to the end-user, so even already compiled binaries can be optimized. Through the execution of twelve well-known benchmarks on two multicore platforms, we show that Geras can improve the processor lifetime by up to 83% and 89% over the standard OpenMP execution and its built-in feature that dynamically adjusts the number of threads, respectively. We also show that Geras outperforms techniques that target performance or energy, which reinforces the need for a specific tool that optimizes aging.